IJCM_304A: A Study on Stigma-Discrimination and Sense of Grip on Disease Experienced by the PLHIV Visiting ART Centre of a Tertiary Care Hospital of Kolkata - Roy Shuvajit; Bandyopadhyay Lina; Sahu Monalisha; Modak Dolanchamp; Paul Bobby (Wolters Kluwer Medknow Publications, 2024)
Background: People Living with HIV face not just a health challenge but also the burden of stigma-discrimination. The impact isn't just physical; it takes a toll on their mental health. Many internalize this stigma, feeling shame about their condition. It Is crucial to address these issues not only for those directly affected but also to build a society that is compassionate and understanding, supporting individuals with HIV/AIDS rather than marginalizing them. Objective: To determine the level of stigma-discrimination faced by PLHIV visiting the ART center of a tertiary care hospital of Kolkata including the factors associated with it. The second objective is to explore their sense of grip on the disease among them. Methodology: This descriptive method study was conducted in November 2023 among 120 PLHIV (Selected by systematic random sampling) visiting the ART center of the School of Tropical Medicine, Kolkata after getting permission from IEC & NACO. Qualitative data was collected via IDI & KII. Quantitative data were analyzed using MS Excel, SPSS v. 16, employing descriptive and inferential statistics. Manual thematic analysis applied for qualitative data. Results: Among 120 participants 45.8% of the participants faced more stigma & discrimination in comparison to others. There was a statistically significant difference in the level of stigma & discrimination based on their age group (p-value 0.033), type of family (p-value 0.014), Addiction status (p-value 0.037), co-morbidities (p-value 0.011), viral load (p-value 0.033). On exploring sense of grip on disease majority of the participants were shown to have a compliant profile. Conclusion: The levels of stigma- discrimination were associated with their behavioral & disease characteristics. Thus, raising awareness is essential to combat stigma and enhance sense of grip on the disease.